Application of lipidomics to reveal differences in facial skin surface lipids between males and females. (3rd January 2018) - Cui, Le; He, Cong‐fen; Fan, Lin‐na; Jia, Yan
Summary: Purpose: To analyze and compare differences in facial skin surface lipids (SSL) between 18‐ to 25‐year‐old males and females. Methods: Ultra‐performance liquid chromatography quadrupole time of flight mass spectrometry (UPLC‐Q‐TOF‐MS) technology was used to measure the facial SSL composition of 18‐ to 25‐year‐old males and females. Measurement results were combined with the orthogonal projections to latent structures discriminant analysis (OPLS‐DA) model for analysis and comparisons, and differences in lipids with significance were selected. Results: There were significant differences in facial SSL composition between 18‐ to 25‐year‐old males and females. Under selected conditions, 37 types of lipids with significant differences were obtained ( P  ≤ .05). All of them had higher content in females, and primarily included ceramides (Cers), glucosylceramide (GlcCer), phosphatidylserine (PS), phosphatidylcholine (PC), and others. Conclusions: There are significant differences in facial SSL between 18‐ to 25‐year‐old males and females.